Partisipasi Pemilih Perempuan Dalam Pilkada Tahun 2024 di Kota Ternate - Faisal, Fatma (Universitas Pahlawan Tuanku Tambusai, 2025)
The purpose of this research is to examine the participation of female voters in the 2024 Regional Head Election in Ternate City, North Maluku Province. This study employs an empirical juridical research method. The empirical juridical research method is a legal research approach that aims to observe law in its practical sense, analyzing and examining how law operates within society. This method also encompasses research on legal identification and the effectiveness of law. The functioning of law in society can be analyzed through aspects such as the level of legal effectiveness, compliance with the law, the role of legal institutions in law enforcement, and the implementation of legal rules in addressing social issues. This research utilizes both primary and secondary data. Primary data is obtained directly from the first-hand sources related to the issues under discussion, while secondary data is gathered through library research, including primary legal materials, secondary legal materials, and tertiary legal materials. The findings of this research reveal that women’s participation in the era of globalization and modernization plays a significant role in various aspects of societal life. Women’s roles are increasingly recognized not only as voters but also as active participants in electoral contests. Efforts to foster awareness and encourage female voters to exercise their voting rights must be conducted consistently. Furthermore, socialization regarding the use of voting rights should be accompanied by education on the prohibition of involvement (both as candidates and voters) in money politics practices.